In(compatibility) of intravenous drugs in critical units: adult cohort - Julia Helena Garcia; Jeiel Carlos Lamonica Crespo; Alina Yukie Handa; Kátia Grillo Padilha; Silvia Regina Secoli
ABSTRACT Objectives: To analyze potential (in)compatibilities of intravenous drugs based on the scheduling prepared by the nursing team. Methods: historic cohort (retrospective) with 110 adults in critical units. Intravenous medications were identified concomitantly, whose pairs were analyzed for (in) compatibility using the screening system Trissel's™ 2 Compatibility IV-Micromedex 2.0. Parametric and non-parametric statistic were used according to the nature of the variable. Results: 565 pairs of drugs were identified. Of these, 44.9% were compatible; and 8.8%, potentially incompatible. Most potentially incompatible pairs involved substances with alkaline pH such as phenytoin (32%) and sodium bicarbonate (8%) and weak acids such as midazolam (12%) and dobutamine (6%), which could result in precipitate formation. Conclusions: almost half of the mixtures simultaneously administrated was compatible, which indirectly reflects in the organized work between the nursing team and the clinical pharmaceutic in the discussions and decisions related to time scheduling.